THE EFFECT OF THINK-PAIR-SHARE MODEL AND MOTIVATION ON STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Al Furqon Al Furqon (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: This study was conducted to find out the effect of Think-Pair-Share model and motivation on students’ reading comprehension achievement. This experimental research applied nonequivalent control group design. The population of this study was in the academic year of 2013/2014. There were four classes divided into two groups as control group and experimental group which consisted of 20 students each. Reading comprehension test along with questionnaire from Teacher Ratings of Student Motivation to Read (TRSM) were used to collect the data. The findings of this study showed that there were significant differences in reading comprehension achievement between before and after the students were taught by using Think-Pair-Share model. In addition, a significant difference in reading comprehension achievement between the students who were taught by using Think-Pair-Share model and those who were taught by using Teacher-Centred method was also found. However, the interaction effect was not found between teaching reading by using Think-Pair-Share model and levels of students’ motivation (high, average, low) on students’ reading comprehension achievement. Key words: Think-Pair-Share Model, Teacher-Centred, motivation, reading comprehension achievement, eight graders